Financial Habits and Their Impact on Consumer Financing Quality in Islamic Banking Institutions - Muhammad Sofyan; Asrid Juniar (Universitas Alma Ata, 2025)
Introduction: This study examines the impact of financial habits on the quality of consumer financing in Islamic banking institutions in Banjarmasin, Indonesia. This topic is crucial as customer financial behavior directly influences the health and stability of an Islamic bank's financing portfolio. Despite its importance, the specific mechanisms through which financial habits influence financing quality, particularly with the involvement of product selection, remain underexplored.Methodology: A quantitative approach was employed, collecting data through a survey of 332 consumer financing customers in Banjarmasin. Data analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM), encompassing the evaluation of the outer model, inner model, and mediation analysis. Result: The empirical findings indicate that financial management habits significantly influence financing product selection, which in turn significantly impacts financing quality. Importantly, product selection mediates the relationship between financial management habits and financing quality. Furthermore, both installment payment habits and saving habits directly and significantly influence the quality of consumer financing.Conclusion: This research concludes that customers' financial habits, particularly financial management, installment payment, and saving, are critical determinants of consumer financing quality in Islamic banking, with financing product selection playing a significant mediating role. The main take-home message is that Islamic banks should integrate comprehensive assessments of customers' financial behaviors into their financing selection processes to strategically improve portfolio quality and effectively minimize default risks.